CONSTRAINED PARADIPLOMACY: SOUTH SULAWESI–EHIME SISTER PROVINCE COOPERATION, 2019–2025 - Reskiyah, Emy Sri; Pusvitasary, Vivi (Department of International Relations Universitas Satya Negara Indonesia, 2026)
In an era of globalization and decentralization, paradiplomacy has emerged as a vital mechanism for subnational governments to navigate international relations. However, the tension between regional autonomy and central oversight remains theoretically and practically underexplored. This study employs a qualitative case study method, using document analysis and semi-structured interviews to examine the sister province partnership between South Sulawesi and Ehime Prefecture. The analysis is grounded in liberal interdependence and constructivist identity-building theories to evaluate the effectiveness of subnational agency within a hierarchical political structure. The results show that while the partnership offers strategic potential in fisheries (technology transfer) and agriculture (the Michi no Eki model), implementation during the 2019–2025 period has been largely normative. Tangible outcomes have been stifled by bureaucratic hurdles, financial asymmetries, and political instability. This study contributes a critical perspective by highlighting potential structural constraints facing subnational diplomacy in Global South.